Experimental, Semi-theoretical, and Theoretical Electronic and Non-linear Optical Characteristics of ECBP - Tanis, Emine; Sas, Emine Babur; Gündüz, Bayram; Kurt, Mustafa (Springer, 2020)
The electronic properties of 4,4 '-bis(3-ethyl-N-carbazolyl)-1,1 '-biphenyl (ECBP) have been studied using time-dependent density functional theory. The non-linear optical (NLO) properties and dipole moments were investigated to understand the optical behavior of ECBP. Frontier molecular orbitals were determined to define the energetic properties of the title molecule. The total density of states, partial density of states, and overlap population electronic density of states of ECBP were calculated and analyzed. Experimental and semi-theoretical parameters such as the optical density, transmittance, absorbance band edge, optical bandgap, refractive index, incidence angle, and refraction angle of ECBP at 3 mM, 10 mM, 21 mM, and 70 mM were obtained. The results indicate that this molecule is a suitable material for NLO, optical, and optoelectronic devices.
Gunduz, Bayram/0000-0002-1447-7534
Keywords: ECBP molecule; optoelectronic devices; experimental; semi-theoretical and theoretical studies; electronic and non-linear optical properties